Solidariedade como princípio constitucional e o humanismo necessário - Ishikawa, Erica Tais Ferrara (2015)
Is this doctoral thesis, under the philosophy of Law and the State, which aims to bring a brief review of the man and the law; the evolution of both the needs that arise from the dynamics of current relationships; the finding that the inertia of the man shows his real selfish concept, and the transition of natural rights into positive law as the legal model willing to safeguard fundamental rights. It is proposed, the present work, to affirm that solidarity is not only as belonging to the ethical or moral demesne, but that, after his provision in the Federal Constitution of 1988, it became legal rule positively valued by constitutional principle. Therefore the need for identification of solidarity or as a rule or a principle in law. The intercultural dialogue is also inserted as a way of realization of the principle of solidarity, because, aim at the protection and realization of fundamental rights. In this sense, the European Union is the best example of diverse cultures, religions and Constitutions, which considers all its inhabitants as citizens, particularly characterized by free movement of person. Given this fundamental right, will be evaluated as the European Court concretize the principle of solidarity provised in the Charter of Fundamental Rights of the European Union. In Brazil, will be verified the application of the principle of solidarity by the decisions of the Supreme Court and it usage translates into a necessary humanism by all jurisdictions